La Lingua dei Segni Italiana (LIS) nella scuola: la prospettiva bilingue ed embodied come risorsa inclusiva per alunni sordi e udenti a partire dai contesti educativi zero-sei - Mignosi, Elena (Studi sulla Formazione/Open Journal of Education, 2023)
Presence of deaf pupils in school, starting from nursery and kindergarten, constitutes a great opportunity to reflect on the inclusion processes and to conceive and experiment pedagogical and methodological-didactic innovations that are enriching for all children, as it involves different interrelated areas, first of all the linguistic-communicative one, essential for cognitive, emotional and relational development, and central to the teaching-learning processes. It also sheds new light on the specifics of human communication, deepening the role of body and space in the intersubjective relationship, adopting a multimodal and embodied perspective. Therefore it promotes, in parallel, new ways of mediation and conducting activities by educators and teachers , not only in pre-school contexts, but also in every eduacational level. In the article I will therefore try to show why, as far as deaf children are concerned, the pedagogical perspective cannot be separated from developmental psychology, psycholinguistics, neurosciences and the historical-cultural perspective. I will then deepen the possible methodological choices if a bilingual perspective is adopted and the achievable objectives for both deaf and hearing children.